Induction of Emetic, Pyrexic, and Behavioral Effects of Staphylococcus aureus Enterotoxin B in the Ferret - Wright, Angela (American Society for Microbiology, 2000)
Ferrets which had been orally dosed with 5 mg of Staphylococcal enterotoxin B (SEB) responded with an increase in subcutaneous temperature. At 75 min, the subcutaneous temperature was significantly higher (+ 0.9°C ± 0.38°C, P < 0.007) than in control animals. Animals dosed with 1 or 2 mg of SEB responded with a small, but not significant, increase in subcutaneous temperature. All of the animals dosed with 5 mg of SEB retched and vomited. The mean latency for the onset of retching was 105 ± 36 min, and the mean latency for the onset of vomiting was 106 ± 34 min. The mean number of retches was 17.8 ± 19.6, and the mean number of vomits was 2.0 ± 1.5. These findings indicate that ferrets can be used as alternatives to primates for the study of the biological activities of SEB.